Momento brasileiro: Reflexões sobre o nacionalismo, a educação musical e o canto orfeônico em Villa-Lobos - Rita de , Cássia Fucci Amato (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2008)
The aim of this paper is to elaborate considerations about the work of Heitor Villa-Lobos in the creation and development of the choral singing in Brazil, understood as a project that involved the nationalist movement as so as educative and social notions referring its relation with the music teaching. In this sense, the nationalist movement in Brazil and its entailment with Vargas government, the historical bases that founded the project of the choral singing, as New School movement, and the social implications appertained to Villa-Lobos’ conception of singing together, are analyzed observing the socialization, the moral formation, the civism, and the patriotism. Therefore, an analysis is made about the ideological implications of choral singing in Vargas’ government.